In Vitro Evaluation of Different Solvents for Retrieval of Mineral Trioxide Aggregate and Calcium-Enriched Mixture - Sadat Shojaee, Nooshin; Adl, Alireza; Sobhnamayan, Fereshteh; Khademi, Azam; Hamedi, Mina (Iranian Endodontic Journal, 2016)
Introduction: The purpose of this study was to evaluate the effect of different solvents; carbonic acid (H2CO3), hydrochloric acid (HCl), chlorhexidine (CHX) and sodium hypochlorite (NaOCl) on the surface hardness of mineral trioxide aggregate (MTA) and calcium-enriched mixture (CEM) cement. Methods and Materials: Plexiglass molds were prepared and filled with Angelus MTA or CEM cement and then exposed to 2% carbonic acid, 37% hydrochloric acid, 2% chlorhexidine, 5.25% sodium hypochlorite and normal saline at intervals of 1 and 21 days, respectively (n=4). Surface microhardness of all specimens was analyzed by a universal testing machine and an electron microscope for some selected samples. Data were analyzed using the three-way ANOVA. Subgroup analysis was performed by Student’s t-test, One-way ANOVA and Tukey’s tests. The level of significance was set at 0.05. Results: On the first day, all solvents and on 21st day HCl, and H2CO3 were more effective in reducing the microhardness of MTA compared to CEM cement (P<0.05). Conclusion: The two experimental cements were differently affected by the solvents at specific time intervals. The solvents were more effective on MTA. Keywords: Calcium-Enriched Mixture; Microhardness; Mineral Trioxide Aggregate; Retrieval